# Calculator search results

Formula
Solve the equation
Graph
$y = 7 x - \left ( \left ( x + 5 \right ) - \left ( 3 x - 1 \right ) \right )$
$y = 12$
$x$Intercept
$\left ( \dfrac { 2 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 6 \right )$
$7x- [ \left( x+5 \right) - \left( 3x-1 \right) ] = 12$
$x = 2$
 Solve a solution to $x$
$7 x - \left ( \left ( x + 5 \right ) \color{#FF6800}{ - } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \right ) = 12$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$7 x - \left ( \left ( x + 5 \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } + \color{#FF6800}{ 1 } \right ) = 12$
$7 x - \left ( \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 12$
 Get rid of unnecessary parentheses 
$7 x - \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 12$
$7 x - \left ( \color{#FF6800}{ x } + 5 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 1 \right ) = 12$
 Calculate between similar terms 
$7 x - \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 5 + 1 \right ) = 12$
$7 x - \left ( - 2 x + \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 12$
 Add $5$ and $1$
$7 x - \left ( - 2 x + \color{#FF6800}{ 6 } \right ) = 12$
$7 x \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \right ) = 12$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$7 x + \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 } = 12$
$\color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } - 6 = 12$
 Calculate between similar terms 
$\color{#FF6800}{ 9 } \color{#FF6800}{ x } - 6 = 12$
$9 x \color{#FF6800}{ - } \color{#FF6800}{ 6 } = 12$
 Move the constant to the right side and change the sign 
$9 x = 12 \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
$9 x = \color{#FF6800}{ 12 } \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
 Add $12$ and $6$
$9 x = \color{#FF6800}{ 18 }$
$\color{#FF6800}{ 9 } \color{#FF6800}{ x } = \color{#FF6800}{ 18 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ 2 }$
 그래프 보기 
Graph
Solution search results